GASTRONOMY TOURISM OF PALM CABBAGE AS A SUPPORTING TOURISM ATTRACTION IN SUROUNDING TAMBING LAKE - Dias Pratami Putri; Yulianto Yulianto (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
A local community has intense interaction with forests that generate the local knowledge how to utilize and sustain of forest resources. Umbut based foods are the local food uniqueness of the Sedoa Community that potentially offered in gastronomic tourism. Currently, there is no local food that has been considered as a tourist attraction in tourism activities in Tambing Lake, Lore Lindu National Park (LLNP). Therefore, the purpose of this paper is to promote umbut based foods as a part of special interest tourism to support tourism in Tambing Lake in LLNP. Data were obtained through in-depth interviews with 12 respondents who were selected purposively. Sedoa Village is located near Tambing Lake tourist attractions, which is the main of TNLL's natural tourism activities. The results showed that there are 8 palm species are possible for promoting of gastronomic tourism. Furthermore, Umbut based foods have a unique variety in flavors and served for different uses for both daily needs and part of community events. Finally, gastronomic tour packages are offered for foreign tourists who are interested in the unique nature and culture in the TNLL